2018
DOI: 10.1371/journal.pone.0190567
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and fatigue in adults with congenital unilateral upper limb deficiency in Norway. A cross-sectional study

Abstract: PurposeTo describe Norwegian adults with congenital unilateral upper limb deficiency (CUULD) regarding self-reported chronic pain (intensity, locations, impact on daily life) and fatigue. Analyze associations between chronic pain and demographic/clinical factors and associations between fatigue and demographic/ clinical factors. Materials and methodsCross-sectional study. In 2012, a postal questionnaire was sent to 186 persons with congenital limb deficiency, age ! 20 years. Seventy seven persons with CUULD re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Fatigue in adults with CUULD has not been investigated previously, and might be important in further studies. In a previous paper [16], we reported severe fatigue among one third of the study population. Furthermore 25% of respondents in the present study reported reduced work capacity.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Fatigue in adults with CUULD has not been investigated previously, and might be important in further studies. In a previous paper [16], we reported severe fatigue among one third of the study population. Furthermore 25% of respondents in the present study reported reduced work capacity.…”
Section: Discussionmentioning
confidence: 86%
“…A high prevalence of chronic musculoskeletal pain has been reported in several studies on persons with congenital and acquired UULD [1618]. Chronic pain is a predictor for work participation in the general population [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations